Experimental studies of a new thermoelectric material based on semiconductor solid solution Ti1-xAlxNiSn - Stadnyk, Yu.; Romaka, V.A.; Romaka, L.; Horyn, A.; Pashkevych, V. (Physics and Chemistry of Solid State, 2024)
The structural, electrokinetic, and energetic properties of the Ti1-xAlxNiSn semiconductor solid solution, obtained by introducing of Al atoms into the structure of the TiNiSn half-Heusler phase by substituting Ti atoms in the crystallographic position 4a, were studied. It is shown that in the range of concentrations x = 0–0.01, Al atoms mainly replace Ni atoms in the 4c position, generating acceptor states. It was established that at temperatures T = 80–160 K, the ratio of concentrations of ionized acceptor and donor states in n-Ti1-xAlxNiSn, х = 0–0.04, is unchanged, but the concentration of donors is greater. At higher temperatures, T ≥ 250 K, deep donor states that existed in n-TiNiSn as a result of "a priori doping" of the semiconductor are ionized. An additional mechanism for the generation of donor states in n-Ti1-xAlxNiSn when the tetrahedral voids of the structure are partially occupied by Al atoms was revealed. The concentration ratio of the generated donor-acceptor states determines the position of the Fermi level εF and the conductivity mechanisms of n-Ti1-xAlxNiSn. The studied semiconductor solid solution is a promising thermoelectric material.